Measurement of total free amino acids content in black tea using electronic tongue technology coupled with chemometrics. (January 2020) - Ouyang, Qin; Yang, Yongcun; Wu, Jizhong; Chen, Quansheng; Guo, Zhiming; Li, Huanhuan
Abstract: The potential of cyclic voltammetry electronic tongue (CVET) coupled to chemometrics was investigated for measuring total free amino acids (FAA) content in black tea. Two working electrodes - glassy carbon electrode and platinum electrode were comparative and syncretic in prediction of total FAA content. Synergy interval partial least square (Si-PLS) combined with variable combination population analysis (VCPA), namely Si-VCPA-PLS, was creatively employed for searching characteristic variables selection from the whole cyclic voltammetry data set. Cyclic voltammetry signals coupled Si-VCPA-PLS model results represented its feasibility in estimating total FAA content in black tea, achieved with R p = 0.8185 for the glassy carbon electrode; R p = 0.8366 for the platinum electrode; and R p = 0.8414 for their data fusion. The extracted characteristic variables were only occupying about 0.2% of the origin. This work confirmed that the cyclic voltammetry electronic tongue could be as a fast, low-cost, efficient and complementary approach for predicting total FAA content in black tea. Highlights: FAA as an important contributor to sensory quality in black tea was sensing by CVET. Glassy carbon and platinum working electrode were used to collect CV signals. CVET combined with Si-VCPA-PLS and data fusion showed best performance.